Avaliação da estrutura cognitiva dos indivíduos face ao ruído de tráfego rodoviário em zonas urbanas - Antunes, S. (2011)
In this paper the evaluation of the cognitive structure of individuals in relation to sources of traffic noise was made by using the semantic differential technique applied to people living in urban areas. Audio recordings of the traffic noise were used as objects. 12 sample sounds were selected, and an analysis in terms of physical and psychoacoustic quantities was made. Subsequently, a principal component analysis was made in order to extract the common factors underlying the 21 pairs of considered adjectives. This analysis was conducted jointly for the 12 samples sounds and, individually, for the sounds due to road traffic, vehicle pass by, rail traffic, and air traffic. Then an association between the adjectives pairs and physical and psychoacoustical aspects was done. In the context of the results of this study, some considerations about the parameters used to quantify the impact of noise in urban areas, and the procedures to globally improve public participation in noise impact assessment are made.